Corporate Governance and Liquidity: An Exploration of Voluntary Disclosure, Analyst Coverage and Adverse Selection as Mediating Mechanisms - GOH, Beng Wee (Institutional Knowledge at Singapore Management University, 2009)
Our paper focus on how voluntary public disclosure, analyst coverage and adverse selection among investors mediate this relation between corporate governance and liquidity. Our results show that better corporate governance, in terms of greater board independence and greater institutional monitoring, is associated with greater liquidity though more voluntary disclosure, greater analyst coverage, and lower adverse selection. The effects of these mediating mechanisms differ in magnitude. Specifically, we find that the main reason to expect a positive association between corporate governance and liquidity is lower adverse selection. To the extent that adverse selection among investors is due to agency problems such as insider trading and selective disclosure to some investors, this finding suggests that the link between corporate governance and liquidity is largely driven by the effect of corporate governance in alleviating these agency problems.